Analisis Kemampuan Berhitung Siswa Diskalkulia melalui Asesmen Pembelajaran Inklusif di SDS Kuncup Mekar (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2026)
This study aims to describe the implementation of assessment processes for basic to advanced numeracy skills among students with special educational needs, specifically those with dyscalculia, at SDS Kuncup Mekar, as well as to examine the forms of inclusive learning support provided by the school. The research employed observational techniques and simple interviews involving two students with different levels of dyscalculia: one lower-grade student with mild learning difficulties and one upper-grade student experiencing more severe challenges. The findings indicate that SDS Kuncup Mekar has implemented equitable educational services for all learners, including students with special needs. At the lower-grade level, students demonstrated significant limitations in recognizing learning materials, following instructions, and performing basic arithmetic operations, which required intensive assistance from teachers and peers. Meanwhile, the upper-grade student showed similar learning barriers but was able to respond more quickly when guided. In addition, teachers adapted the level of task difficulty, provided direct instructional support, and collaborated with parents through therapeutic interventions and supplementary learning activities. Overall, this study highlights that appropriate assessment practices and inclusive learning support play a crucial role in facilitating the optimal development of numeracy skills in students with dyscalculia.